Root iron uptake efficiency of Ulmus laevis and U. minor and their distribution in soils of the Iberian Peninsula - Venturas, Martin (Frontiers Media S.A., 2014)
The calcifuge and calcicole character of wild plants has been related to nutrient availability shortages, including iron (Fe)-deficiency. Surprisingly, just a few studies examined the relation between root Fe uptake and plant distribution in different soil types. We assessed the root Fe acquisition efficiency of two Ulmus species with calcareous (Ulmus minor) and siliceous (U. laevis) soil distribution patterns in the Iberian Peninsula. Seedlings of both elm species were grown hydroponically with different Fe concentrations during 6 weeks. Plant physiological responses to Fe-limiting conditions were evaluated as were the ferric reductase activity and proton (H(+)) extrusion capacity of the roots. Iron deprived elm seedlings of both species were stunted and suffered severe Fe-chlorosis symptoms. After Fe re-supply leaf chlorophyll concentrations rose according to species-dependent patterns. While U. minor leaves and seedlings re-greened evenly, U. laevis did so along the nerves of new growing leaves. U. minor had a higher root ferric reductase activity and H(+)-extrusion capability than U. laevis and maintained a better nutrient balance when grown under Fe-limiting conditions. The two elm species were found to have different Fe acquisition efficiencies which may be related to their natural distribution in calcareous and siliceous soils of the Iberian Peninsula.